The Murder of Captain William Francis: An Incident in the War of 1812 - Garrad, Charles (Ontario History, 2019)
Captain William Francis was murdered in the land war in Canada in the War of 1812. Was he an innocent farmer murdered in his bed by American partisans as part of some larger military strategy or was his death more personal in nature? This article concludes that the murder was the result of personal antagonism between John Dickson, the murderer, and William Francis of many years duration newly exacerbated by the testimony given against a number of Dickson’s gang. This feud had repercussions in a number of actions during the war including the Sutherland Raid, the Port Rowan, Port Dover, and McCrae incidents, and the Battle of Nanticoke. This article shows that, for some, the war was an opportunity to settle personal scores.